Workers' Strikes in Local Films and Made in Dagenham Narratives - Umali, Mary Anne Claire M. (Review of Women's Studies; Vol 26 No 1-2 (2016): Review of Women's Studies Volume XXVI, Numbers 1-2 (January-December 2016), 2023)
This paper examines local films that tackle the subject of worker's strikes that had women characters in comparison to the British film, Made in Dagenham, which was about a strike led by women in 1968 and spurred political debate, leading to the United Kingdom's Equal Pay Act 1970.